Influence of motion parameters of the drying agent on kinetics of mixed heat transfer drying - Погожих, Микола Іванович; Пак, Андрій Олегович; Пак, Аліна Володимирівна; Жеребкін, Максим Васильович (Eastern-European Journal of Enterprise Technologies, 2014)
The paper deals with studying the influence of motion parameters of the drying agent on the kinetics of mixed heat transfer drying for obtaining the requirements to functional features of turbulators, used in drying by this method. It was noted that one of the promising drying methods in terms of increasing the dehydration intensity, reducing specific energy consumption per unit of dried products and preserving the feedstock quality is mixed heat transfer drying. Installation for studying the influence of motion parameters of the drying agent on the temperature kinetics and the moisture content kinetics of feedstock during MHT-drying was designed and built. Based on studies of temperature kinetics and moisture content kinetics of feedstock at different angles of blowing of mass transfer gaps by drying agent from the range 0°–90° it was found that the temperature kinetics of feedstock at the investigated blowing angles are of nature, typical for the MHT-process. It was determined that the dehydration duration is the longest for blowing angles 25°–35°, time the thermogram achieves local minimum and, respectively, maximum of drying speed for this range is the latest. It was found that at increasing and decreasing the blowing angle with respect to this range, drying duration reduces and maximum dehydration speed is reached earlier. It is noted that inserts-turbulators, which are structural features of MHTdryers, must provide blowing of FC mass transfer gaps by drying agent at angles, close to rational, which are the angles 0° and 60°.